Analisis Pengaruh Visionary Leadership Terhadap Organization Innovation yang Dimediasi oleh E-Leadership dan Dimoderasi ICT Awareness pada Universitas Swasta di Kota Sorong Papua - Ade Andriani Renouw; Ferdi Antonio (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effect of visionary leadership on organizational innovation mediated by e-leadership and moderated by ICT awareness. This study used a quantitative approach that was non-experimental by collecting information through a questionnaire. This research was conducted at four private universities in Sorong City, Papua. The population in this study were the Dean, Head of the Study Program, Staff and Lecturers, as many as 530. The data analysis technique in this study used Smart PLS. The results of this study indicated that there was an influence between visionary leadership on organizational innovation, which was moderated by e-leadership and mediated by ICT awareness. Still, there was no significance in the hypothesis testing, namely hypotheses 1 and 2.